Risk factors for omphalitis in neonatal dairy calves - Meier, Kim K.; Stock, Annegret; Merle, Roswitha; Arndt, Heidi; Dachrodt, Linda; Hoedemaker, Martina; Kellermann, Laura; Knubben-Schweizer, Gabriela; Volkmann, Maria; Müller, Kerstin-Elisabeth (Frontiers in Veterinary Science, 2024)
Knowledge about potential risk factors for animal health is crucial to achieve animal welfare. The aim of this study was to provide practical guidance for farmers to improve the health status of their youngstock by identifying and eliminating risk factors for omphalitis in neonatal calves. A cross-sectional study including 3,445 dairy calves from 567 farms located in three structurally different regions of Germany was performed from December 2016 to July 2019. On each farm calves aged five to 21 days underwent clinical examinations with special consideration of the umbilicus for signs of inflammation. Information regarding animal health, hygiene, and management was obtained via interviews with the farmers. Rearing conditions were recorded following visual inspection using written standard operating procedures. Multifactorial statistical analyses were performed to identify potential risk factors for omphalitis on animal and farm level. The overall omphalitis prevalence in calves aged five to 21 days was 30.9%. Across all regions and farms, every fourth calf per farm exhibited signs of omphalitis (median farm prevalence: 25.0%, interquartile range: 0.0–50.0%). According to the farmers, however, only 4.5% of the calves had been treated for omphalitis in the preceding 12 months. Risk factors for omphalitis identified included the dampness of the lying area in the first 2 weeks of life, a body condition score of the dam after calving outside the optimal range, and the time that calves spent with their dam after birth. Calves on farms providing dry lying areas in the first 2 weeks of life had 0.77 times the risk of omphalitis compared to calves on farms with predominantly damp bedding. When the dams were judged under- or over-conditioned after calving, their offspring had a 1.4 times higher omphalitis risk, respectively, compared to calves from dams optimal conditioned. Calves from farms separating calf and dam beyond 12 h after birth were 0.75 times as likely to develop omphalitis than calves from farms performing immediate separation. These results highlight the complexity of multifactorial diseases such as umbilical infection. The evidence presented can help to establish guidelines for dairy farmers to improve the umbilical health of their calves.